2004
DOI: 10.7863/jum.2004.23.8.1011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fetal Pulmonary Vasculature by Power Doppler Imaging in Congenital Diaphragmatic Hernia

Abstract: Objective. To evaluate the feasibility of prenatal power Doppler imaging of pulmonary arteries in congenital diaphragmatic hernia and to study its potential to predict outcome. Methods. A prospective observational study was conducted. Forty-two cases of congenital diaphragmatic hernia (32 left and 10 right) without associated anomalies were analyzed. Qualitative evaluation of pulmonary vasculature was based on power Doppler imaging performed at 26 to 38 weeks. The pulmonary arteries were studied in the lung co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
(45 reference statements)
2
21
0
2
Order By: Relevance
“…Two previous studies have used power Doppler methods to assess changes in CDH. Mahieu-Caputo et al [18] qualitatively assessed the pulmonary vasculature using conventional 2D power Doppler imaging and classified cases in severity stages according to the number of divisions of pulmonary arteries that could be visualized. Cases with fewer than 3 divisions had a higher neonatal mortality rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two previous studies have used power Doppler methods to assess changes in CDH. Mahieu-Caputo et al [18] qualitatively assessed the pulmonary vasculature using conventional 2D power Doppler imaging and classified cases in severity stages according to the number of divisions of pulmonary arteries that could be visualized. Cases with fewer than 3 divisions had a higher neonatal mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies in fetuses with severe pulmonary hypoplasia have reported increased impedance in Doppler vascular blood flow of the intrapulmonary vessels [15][16][17] . In addition, 2 studies have suggested that semiquantitative evaluation of the density of pulmonary vessels estimated by 2D [18] and 3D [19] power Doppler imaging could help to stratify the likelihood of survival in CDH fetuses managed expectantly in utero. Experimental evidence suggests that TO has beneficial effects in the remodeling of the pulmonary arteries, thinning the muscularized pulmonary vessel walls and reducing volume density in pulmonary arteries [20][21][22] .…”
mentioning
confidence: 99%
“…Earlier studies using semiquantitative methods demonstrated that there is a correlation between the degree of lung perfusion and the severity of CDH [19,20] . More recently, fractional moving blood volume (FMBV), a quantitative method validated against gold standards for fetal evaluation [21] , was used to demonstrate that lung tissue perfusion was reduced in CDH and correlated positively with the o/e LHR [22] .…”
Section: Introductionmentioning
confidence: 99%
“…A presença de polihidrâmnio em casos com HDC é explicada pela compressão mediastinal e do esôfago, levando a menor deglutição de líquido amniótico pelo feto. Porém, outros autores não confirmam essa correlação 29,77 . O desvio grave do mediastino correlacionou significativamente com mau prognóstico em alguns estudos 9,29 , o que não é confirmado em outros 41,73,79 .…”
Section: Etiologia E Fisiopatologiaunclassified
“…A presença de polihidrâmnio é um exemplo clássico. Resultados iniciais demonstram haver relação desse achado com óbitos neonatais 9,73,74 , porém isso não foi confirmado em outras pesquisas 29,77 nem no presente estudo.…”
Section: Avaliação Dos Outros Fatores Clássicos De Prognóstico Pela Uunclassified